Epidemiology and initial management of pulmonary arterial hypertension: real‐world data from the Hellenic pulmOnary hyPertension rEgistry (HOPE). (1st October 2019) - Arvanitaki, Alexandra; Boutsikou, Maria; Anthi, Anastasia; Apostolopoulou, Sotiria; Avgeropoulou, Aikaterini; Demerouti, Eftychia; Farmakis, Dimitrios; Feloukidis, Christos; Giannakoulas, George; Karvounis, Haralambos; Karyofyllis, Panagiotis; Mitrouska, Ioanna; et al.
Abstract : Pulmonary arterial hypertension (PAH) is a heterogenous clinical entity with poor prognosis, despite recent major pharmacological advances. To increase awareness about the pathophysiology, epidemiology, and management of the disease, large national registries are required. The Hellenic pulmOnary hyPertension rEgistry (HOPE) was launched in early 2015 and enrolls patients from all pulmonary hypertension subgroups in Greece. Baseline epidemiologic, diagnostic, and initial treatment data of consecutive patients with PAH are presented in this article. In total, 231 patients with PAH were enrolled from January 2015 until April 2018. At baseline, about half of patients with PAH were in World Health Organization functional class II. The majority of patients with PAH (56.7%) were at intermediate 1‐year mortality risk, while more than one‐third were low‐risk patients, according to an abbreviated risk stratification score. Half of patients with PAH were on monotherapy, 38.9% received combination therapy, while prostanoids were used only in 12.1% of patients. In conclusion, baseline data of the Greek PAH population share common characteristics, but also have some differences with other registries, the most prominent being a better functional capacity. This may reflect earlier diagnosis of PAH that in conjunction with the increased proportion of patients with atypical PAH could partially explain the preference for monotherapy and the limited use of prostanoids in Greece. Nevertheless, early, advanced specific therapy is strongly recommended.